Evaluation of a bovine cathelicidin ELISA for detecting mastitis in the dairy buffalo: Comparison with milk somatic cell count and bacteriological culture. (February 2020) - Puggioni, Giulia Maria Grazia; Tedde, Vittorio; Uzzau, Sergio; Guccione, Jacopo; Ciaramella, Paolo; Pollera, Claudia; Moroni, Paolo; Bronzo, Valerio; Addis, Maria Filippa
Abstract: A recently developed bovine cathelicidin (CATH) ELISA was evaluated in the dairy buffalo ( Bubalus bubalis ) by testing 618 quarter milk samples from a herd with subclinical mastitis cases. Somatic cell count (SCC) and bacteriological culture (BC) were carried out on the same samples for comparison. Out of 618 quarters, 258 (41.75%) were positive to CATH, 289 (46.76%) had SCC > 200, 000 cells/mL, and 457 (73.95%) were positive to BC. The most prevalent microorganism was Staphylococcus aureus (SAU, 35.76% of all quarters), followed by non-aureus staphylococci (NAS, 22.17% of all quarters). Clinical mastitis quarters were only 7 (1.13%). CATH levels were significantly higher in clinical quarters and in high SCC, BC-positive quarters than in healthy, low SCC, BC-negative quarters. The highest median values were observed for SAU and the lowest for NAS. Differences among microorganism classes were generally more significant for SCC than for CATH. Test characteristics of the CATH ELISA, evaluated by considering as true positives all BC-positive quarters with SCC > 200, 000 cells/mL ( N = 242), and as true negatives all sterile quarters with SCC < 200, 000 cells/mL ( N = 44), were as follows: sensitivity 57.85%, specificity 84.09%, positive predictive value 95.24%, negative predictive value 26.62%, accuracy 61.89%. Therefore, the bovine CATH ELISA showed a fair sensitivity and a good specificity in detecting water buffalo mastitis. Graphical abstract: Unlabelled Image Highlights: A bovine/ovine cathelicidin ELISA was evaluated for detecting mastitis in buffaloes. The cathelicidin ELISA showed good specificity and fair sensitivity. Optimization on species-specific sequences might further improve diagnostic performance.